Ensaios sobre as associações do consumo de cannabis com o índice CCEB, as preferências sobre a legalização e o desempenho universitário dos estudantes efetivamente matriculados - Alvaro Alberto Ferreira Mendes Junior (2018)
This thesis intends to contribute to the debate about the best public policy for Cannabis available in Brazil and has four main objectives: (i) to verify the associations between the socioeconomic index CCEB and the Cannabis consumption of the Brazilian university students; (ii) analyze the associations of chronic consumption of Cannabis with the progression of students actually enrolled in Brazilian universities; (iii) present a discussion of the forces driving legalization movements in the West; and (iv) to examine the associations of different patterns of consumption with the support to Cannabis legalization in Brazil. In order to answer the proposed objectives, bibliographical reviews, descriptive statistics and econometric regressions were applied to the two main databases of Brazilian drug users, the 1st Nationwide Survey on the Use of Alcohol, Tobacco and Other Drugs among College Students in the 27 Brazilian State Capitals of FM/USP and the 2nd National Survey on Alcohol and Drugs (II LENAD) of INPAD / UNIFESP. The main findings for each of the objectives listed were: (i) Cannabis is the illicit drug with the highest proportion of recreational consumption in this population. In addition, individuals from classes A and B of the CCEB index are associated with a 120% greater chance of marijuana use in the last 12 months when compared to classes C, D and E. (ii) Our best estimates indicate that a moderate or high risk of dependence on Cannabis was associated with a decrease in the probability of be approved in all disciplines (without take a final exam) on the Linear Probability Model (MPL) by 4.9% and in MPL-VI by 33.6%. In the probit and bivariate probit models, the reduction was 5.2% and 9.8%. The associations between consumption and worse educational performance were negative in the 20 presented models, being significant at the level of 10% in 13 of them. (iii) marginalized users; the Cannabis subculture; recreational and dependent users; the prolegalization experts and progressive philanthropic; and the Cannabis industry are the main supporters of legalization movements in the West. (iv) The self-interest component of Cannabis use is the main determining factor for legalization support of the substance in Brazil. Thus recreational users are associated with a 20.6 times greater risk of supporting marijuana legalization than non-users.